Ketimpangan Pendidikan di Nusa Tenggara Timur: Evaluasi Kurva Kuznet dan Determinannya - Novianti Banunu (Jurnal Statistika Terapan (ISSN 2807-6214), 2021)
Education plays an important role in social and economic development. This study have calculated two measures of inequality in education: Gini coefficient of education and the standard deviation of schooling to identify the existence of Kuznets curve and also analyze the inequality of education in East Nusa Tenggara. Data used in this study comprises cross sectional data from 22 regencies over the period 2015-2020. Hierarchical clustering has used to control for the heterogeneity of regencies and generate clusters based on social-economic development. The findings show that Kuznets curve exists in high-developed regencies once used the Gini coefficient as approximate the inequality as well as standard deviation of schooling. The existence of Kuznets curve of education in high-developed regencies: As the average level of education rises, education inequality also increases, and after reaching a peak at 8.39 years of schooling, it starts declining. This result also show that the education distribution more equal in high-developed regencies than in middle-developed regencies. The significant variables determining the education inequality in East Nusa Tenggara are percentage of poor population, percentage of illiterate and Gross Domestic Regional Product (GDRP) growth.